Estrés visual y su influencia en la determinación refractiva en docentes de la Unidad Educativa José María Estrada Coello, Babahoyo Los Ríos, octubre 2018 - abril 2019 - Camacho Quinde, Rosa Elena (2019)
Introduction.- This research investigates how the increase and incorporation of electronic devices in the workplace, educational, family and social to stay long hours in front of computers favoring the appearance of visual problems, such as fatigue or eye stress is the response of the eye against excessive muscular effort over a long period of time and refractive errors. Objectives.- The aim is to establish the influence of visual stress on refractive determination in teachers of the Educational Unit "José María Estrada Coello", Babahoyo, Los Ríos, October 2018 - April 2019. Methodology.- This project is an explanatory descriptive research, with a temporal and prospective dimension, taking as sample the totality of the teachers that work in the Educational Unit "José Maria Estrada Coello", applied survey techniques, direct observation and the documented review. Results.- A greater percentage of the female gender was evidenced with 96% of the male population of 4% with visual problems due to visual stress. The majority of teachers (as), are older than 36 years, although the superior rank is in the age of 47 to 57 years of age with 40%. 64% if they have noticed changes in their vision when they are stressed in their daily days. Conclusions.- Among the refractory defects, presbyopia is present in 32 teachers surveyed, or 64% of the population has the highest incidence, followed by hyperopia with 20% and stigmatism with 16%.